USM, HUAWEI WORKING TOWARDS ENHANCING GRADUATE EMPLOYABILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 November 2016 – Challenges for universities would be more demanding in the 21 century especially in preparing students to meet and suit the global requirements of today and the future.